Molecular characterization and pathogenicity of novel Malaysian chicken astrovirus isolates - Abdullahi Raji, Abdullahi; Ideris, Aini; Bejo, Mohd Hair; Omar, Abdul Rahman (Taylor and Francis Group, 2022)
Chicken astrovirus (CAstV) has for over a decade been associated with runting stunting syndrome, severe kidney disease and visceral gout, and white chick syndrome. However, knowledge of the molecular characteristics and pathogenicity of the virus in day-old specific pathogen-free (SPF) chicks is scarce. This study focused on the characterization of near-complete genome of three Malaysian CAstV isolates following virus propagation in SPF embryonated chicken eggs and pathogenicity in day-old SPF chicks. The three isolates demonstrated unique features including a point mutation in their intergenic regions and an additional stem-loop II-like motif (s2m) in ORF-2. Pairwise sequence comparison and phylogenetic analysis of the ORF-2 amino acid sequence of the three isolates revealed an identity share of 86–91% with group B CAstVs while forming a new subgroup in addition to the known four subgroups (Bi, Bii, Biii and Biv) that exhibit high identity of between 95% and 100% within the subgroups. In the pathogenicity study, birds in the infected and exposed sentinel groups exhibited lethargy and diarrhoea 3 days post-inoculation (dpi) that declined by 6 dpi, and 20% growth retardation by 9 dpi. Mild lymphocytic aggregates in the duodenum, tubular degeneration and interstitial nephritis were observed in the intestines and kidneys, respectively, in both groups. In addition, the mean virus copy numbers of the cloacal swabs were log10 13.23 at 3 dpi and log10 9.04 at 6 dpi for the infected and exposed sentinels, respectively. The study suggests that the Malaysian isolates should be assigned to a new subgroup, Bv within group B CAstV.